Exploring spatio‐temporal trends and environmental drivers of wildfire occurrence and impacts in Côte d'Ivoire, West Africa. (1st October 2022) - Kouassi, Jean‐Luc; Wandan, Narcisse; Mbow, Cheikh
Abstract: Wildfires are a significant threat to environmental, social, economic and agricultural systems. This study investigated the spatiotemporal trends in wildfire activity and its interactions with climate and environmental factors in Côte d'Ivoire through remotely sensed MODIS data associated with climate, biophysical and anthropogenic data. We analysed relationships between wildfire occurrence and climate drivers using cross‐correlations, while Pearson chi‐squared and Kruskal–Wallis tests were selected to identify linkages between qualitative and quantitative environmental data, respectively. Seasonal Kendall and Sen's slope approaches were applied for trend analysis. During the period 2001–2019, 8150 wildfires were recorded annually, burning 2.69 million hectares per year, representing about 8.34% of Côte d'Ivoire. Fire detections and burnt areas highlighted a downward trend in all ecoregions with a predominance in the Sudanian zone. Wildfire occurrence showed a significant and strongly negative link with relative humidity and visibility, as well as a significant and positive correlation with maximum temperature, thermal amplitude and vapour‐pressure deficit. Also, the spatial distribution of wildfires was significantly conditioned by environmental factors. The findings of this study will help decision makers and managers to make decisions to reduce the vulnerability of local populations to current and future wildfire hazards. Résumé: Les incendies de forêt constituent une menace importante pour les systèmes environnementaux, sociaux, économiques et agricoles. Cette étude a examiné les tendances spatio‐temporelles des feux de forêt et leur lien avec les facteurs climatiques et environnementaux en Côte d'Ivoire, en s'appuyant sur des données MODIS détectées à distance et associées à des données climatiques, biophysiques et anthropiques. Nous avons analysé les liens entre l'occurrence des incendies de forêt et les facteurs climatiques à l'aide de corrélations croisées, tandis que les tests du chi carré de Pearson et de Kruskal‐Wallis ont été sélectionnés pour identifier les liens entre les données environnementales qualitatives et quantitatives, respectivement. Une approche reposant sur les tests saisonniers de calcul de la pente de Kendall et Sen a été appliquée aux fins d'analyse des tendances. Entre 2001 et 2019, 8 150 incendies de forêt brûlant 2, 69 millions d'hectares par an, soit environ 8, 34 % de la superficie de la Côte d'Ivoire, ont été enregistrés chaque année. Les détections d'incendies et les surfaces brûlées ont mis en évidence une tendance à la baisse dans toutes les écorégions avec une prédominance dans la zone subsaharienne. L'occurrence des incendies de forêt a montré un lien significatif et fortement négatif avec l'humidité relative et la visibilité, ainsi qu'une corrélation significative et positive avec la température maximale, l'amplitude thermique et le déficit de pression de vapeur. Par ailleurs, la répartition spatiale des incendies de forêt a été fortement conditionnée par les facteurs environnementaux. Les conclusions de cette étude aideront les décideurs et les gestionnaires à prendre des décisions visant à réduire la vulnérabilité des populations locales aux risques d'incendies de forêt actuels et à venir.